2005
DOI: 10.1105/tpc.104.029694
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Eukaryotic Nitrate Reduction: Crystal Structures of the Nitrate Reductase Active Site

Abstract: Nitrate assimilation in autotrophs provides most of the reduced nitrogen on earth. In eukaryotes, reduction of nitrate to nitrite is catalyzed by the molybdenum-containing NAD(P)H:nitrate reductase (NR; EC 1.7.1.1-3). In addition to the molybdenum center, NR contains iron-heme and flavin adenine dinucleotide as redox cofactors involved in an internal electron transport chain from NAD(P)H to nitrate. Recombinant, catalytically active Pichia angusta nitrate-reducing, molybdenum-containing fragment (NR-Mo) was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 51 publications
(72 reference statements)
2
122
1
3
Order By: Relevance
“…1 and Table I). The Mo-MPT and dimer interface domains of the nitrate-reducing module have recently been shown (29) to be closely associated as in mammalian and plant SOX (9, 30). Hinge 1 joins the Cyt b domain to the nitrate-reducing module.…”
Section: Resultsmentioning
confidence: 99%
“…1 and Table I). The Mo-MPT and dimer interface domains of the nitrate-reducing module have recently been shown (29) to be closely associated as in mammalian and plant SOX (9, 30). Hinge 1 joins the Cyt b domain to the nitrate-reducing module.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the pterin might also participate in the electron transfer to or from molybdenum via the delocalized electrons within the pterin (5). X-ray crystallographic analyses of molybdenum enzymes revealed that the cofactor is not located on the surface of the protein but is buried deeply within the interior of the enzyme, and a tunnel-like structure makes it accessible to the cognate substrates (12,13). During its lifetime, the molybdenum enzyme does not liberate Moco.…”
Section: What Is the Molybdenum Cofactor?mentioning
confidence: 99%
“…This causes the bond between this O atom and nitrate to break, forming nitrite which is subsequently released. Finally, transfer of two electrons and two protons from NAD(P)H via a cytochrome b5 domain cause regeneration of Mo 4 + and reduction of the O atom bound by a double bond to a water ligand [125].…”
Section: Ec 171: Oxidoreductases Acting On Other Nitrogenous Compoumentioning
confidence: 99%